Legal Aspects of Patients’ Rights from the Perspective of Health Law According to Law Number 17 of 2023 - Robby Franata; Tiarsen Buaton; Tri Agus Suswantoro (CV. Green Publisher Indonesia, 2026)
The transformation of the healthcare system in Indonesia through the enactment of Law Number 17 of 2023 concerning Health represents an important step in strengthening legal protection for patients. The law aims to ensure that patients receive proper healthcare services, clear medical information, and legal protection within the doctor–patient relationship. However, limited awareness and understanding of patient rights among both healthcare providers and patients often contribute to medical disputes and ineffective implementation of legal provisions. Therefore, an analysis of patients’ rights from the perspective of health law is necessary to clarify their legal position and implications in healthcare services. This study aims to analyze the legal aspects of patients’ rights under Law Number 17 of 2023. The research employs a normative juridical method with a qualitative approach. Data were collected through library research and document analysis of statutory regulations, legal doctrines, and relevant scholarly literature obtained from reputable academic sources. The data were analyzed using qualitative descriptive and juridical interpretation to understand the regulation and implementation of patients’ rights in Indonesia’s health system. The results show that the law strengthens patient protection by regulating fundamental rights such as the right to obtain health information, the right to appropriate healthcare services, the right to consent to or refuse medical treatment, the right to access medical records, and the right to seek a second opinion. These provisions reinforce patient autonomy and promote a more balanced doctor–patient relationship in healthcare practice.